CRA-W DISTRIBUTED MENTOR PROGRAM SUPPORTS WOMEN IN COMPUTING. (Computer (00189162), 2009)
The article features the CRA-W Distributed Mentoring Program which was established by the Computer Research Association Committee on the Status of Women in Computing Research (CRA-W) and expanded to become Distributed Research Experiences for Undergraduates (DREU) to cater to qualified undergraduates to be trained by a faculty mentor for 10 weeks. The purpose of the program is to provide an overview of graduate school and increase their competitiveness in taking graduate admissions and fellowships.